Quantitative changes in the protein and miRNA cargo of plasma exosome-like vesicles after exposure to ionizing radiation. (3rd June 2017) - Yentrapalli, Ramesh; Merl-Pham, Juliane; Azimzadeh, Omid; Mutschelknaus, Lisa; Peters, Carsten; Hauck, Stefanie M.; Atkinson, Michael J.; Tapio, Soile; Moertl, Simone
Abstract: Purpose: Multiple cell types secrete exosome-like extracellular vesicles (ELVs) to the extracellular environment. Pathological conditions can produce characteristic changes to the vesicle cargo. We investigated if ionizing radiation is capable of inducing changes in the protein and microRNA (miRNA) cargo of ELVs. Materials and methods: Whole blood samples from healthy donors were irradiated with 2 Gy gamma rays and then peripheral blood mononuclear cells and plasma were separated from residual blood and co-cultivated for 24 h. The released ELVs were collected by differential ultracentrifugation from irradiated and non-irradiated samples. microRNAs and proteins were quantified by qPCR and label-free proteomics. Results: Here we report a first characterization of radiation-induced changes in the protein and miRNA cargo of ELVs isolated from plasma. Proteome analysis of ELVs identified 214 proteins, of which nine significantly changed their abundance after irradiation. The radiation-induced down-regulation of afamin and serpine peptidase F1 was confirmed by immunoblotting. miRNA expression profiling identified 58 different exosomal miRNAs, the expression of miR-204-5p, miR-92a-3p and miR-31-5p was significantly increased in ELVs from irradiated samples. Conclusions: This study provides evidence that radiation-induced changes occur in the protein and miRNA cargo of plasma ELVs. These data imply a novel systemic communication pathway between irradiated and non-irradiated cells and tissues.